Too Many Cards on the Table? Practical Ways of Improving Your Current Awareness. (December 2021) - Brown, Clare
Abstract: This article by Clare Brown is based on a presentation given at the BIALL Online Annual Conference in June 2021. It takes the form of a case study that illustrates how library and information professionals can control the flow of information so as to avoid users being overwhelmed by news.